2017
DOI: 10.1097/md.0000000000006682
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge deficiency of work-related radiation hazards associated with psychological distress among orthopedic surgeons

Abstract: Knowledge and concern degree about work-related radiation hazards remained unknown among orthopedic surgeons. The aim of the cross-sectional study is to investigate whether the knowledge degree of work-related radiation is associated with psychological distress among orthopedic surgeons. This cross-sectional study sent electronic questionnaire via WeChat to orthopedic surgeons nationwide. Concern and knowing degree over radiation exposure was evaluated by a single self-reported question. Professional evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
(33 reference statements)
0
11
0
1
Order By: Relevance
“…Similarly, 82% of anesthesia residents in the United States were found to have very high or high levels of concerns about radiation hazards. 13 With regard to the Asia-Pacific region, Fan et al 14 found that 78.2% of orthopedic surgeons in China considered radiation exposure to be an issue of great concern.…”
Section: Awareness About Radiation Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, 82% of anesthesia residents in the United States were found to have very high or high levels of concerns about radiation hazards. 13 With regard to the Asia-Pacific region, Fan et al 14 found that 78.2% of orthopedic surgeons in China considered radiation exposure to be an issue of great concern.…”
Section: Awareness About Radiation Hazardsmentioning
confidence: 99%
“…In order to protect themselves against radiation exposure, 78.5% of the participants of this study wore a thyroid shield, but only 31.3% of them wore lead goggles. Another study 14 that was conducted among orthopedic surgeons found that 35%, 3%, and 6% of them preferred to use a mobile lead shield than wear protective apparel, wore lead glasses, and worked without a personal protective device, respectively. Similarly, another survey that was conducted in Nigeria in 2013 15 found that only 12%, 5%, and 3% of radiographers consistently wore a lead apron, lead goggles, and a thyroid shield in their work environments, respectively.…”
Section: Awareness About Radiation Hazardsmentioning
confidence: 99%
“…Among all the participants, the ST surgeons showed a higher rate of concern than the other groups, and this may be related to them performing a higher proportion of the FGI procedures than other doctors. Previously, a lack of radiation knowledge and awareness about fluoroscopy were also associated with a high level of concern and low rate of wearing the protective devices [15,16]; therefore, education about radiation exposure is warranted for orthopedic surgeons.…”
Section: Personal Protective Equipment Usementioning
confidence: 99%
“…Diverse harmful effects, such as cancer, cataracts, chromosomal abnormalities, and other chronic diseases, have also been reported in physicians performing FGI procedures globally [14]. In addition, orthopedic surgeons have concerns about the hazards of radiation, but they have been shown to demonstrate lower rates of wearing personal protective equipment and dosimeters [15,16]. However, previous studies on orthopedic surgeons were mainly limited by the small sample sizes and limited information on the FGI procedure-related work practices and occupational radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos internacionais anteriores mostram que os ortopedistas possuem uma percepção do risco ocupacional, mas não possuem conhecimento adequado dos riscos da exposição à radiação, nem noção da dose de radiação em sua prática. [2][3][4][5][6] É fundamental que os ortopedistas tenham percepção dos riscos de exposição à radiação, formas de proteção e controle da exposição individual para a minimização de danos. 7 Este estudo tem por objetivo analisar as percepções dos médicos ortopedistas em relação à exposição à radiação ionizante em sua prática.…”
Section: Introductionunclassified